THE EFFECT OF SLEEP DEPRIVATION ON SERUM IGG RESPONSES TO AEROBIC ACTIVITY IN COLLEGE STUDENT ATHLETES - Jamshidi Far Saeed; Hossein Norouzi Kamareh Mirza (Physical Education of Students, 2014)
Background & Aims: Sleep is a restorative process for the immune system. There are many situations in which sleep is disturbed prior to an athletic event. However, the effect of sleep deprivation on immune indices in response to exercise remains unknown. The aim of this study was to investigate the effects of sleep deprivation on serum IgG responses to aerobic activity. Materials & Methods: In this quasi-experimental study, 10 male physical education students were voluntarily participated. Study was performed in two separate occasions; control and experimental within two weeks. In the control occasion, normal sleep and aerobic activity and in the experimental occasion, sleep deprivation and aerobic activity was applied. Aerobic activity was performed on bicycle ergometer for 30 minutes at intensity of 70 to 75 percent of maximum heart rate. Changes in serum IgG concentrations in pre-test, before and after aerobic activity in both occasions were analyzed by the two repeated measures ANOVA and dependent T-test using SPSS software. Results: The results showed that sleep deprivation not significantly effect on Serum IgG response to aerobic activity (p=0.130). Also, aerobic activity not significantly effect on Serum IgG concentration (p=0.357). But sleep deprivation caused a significantly increase in serum IgG concentration (p=0.035). Conclusion: No significant effect of sleep deprivation on serum IgG concentrations response to aerobic activity.